Indoor air pollutants in schools and their relationship with airway inflammation, respiratory and allergic symptoms among school children in Hulu Langat, Malaysia - Mohd Isa, Khairul Nizam (2021)
Many recent reviews and research have found that interaction exposure to indoor pollutants and a spectrum of allergens can cause allergic reactions, raise the likelihood of developing asthma and exacerbate existing asthma. This study aimed to investigate the relationships between indoor air pollutants, the diversity of fungal relative abundance in the settled dust samples, respiratory and allergic symptoms, and airway inflammation levels (FeNO levels and expression of adhesion molecules) among school children in urban and suburban areas. This comparative cross-sectional study was conducted in the Hulu Langat District, Selangor, Malaysia and involved eight secondary schools located in urban and suburban areas respectively. The indoor air concentration of NO2, CO2, PM10, PM2.5, formaldehyde, as well as temperature and relative humidity were measured using active and passive sampling techniques from 4 classrooms in each school. The settled dust samples were collected inside the classrooms using a vacuum cleaner and further analysed using metagenomic techniques to characterise the fungi composition. The personal and health information were collected among 470 school children aged of 14 years old, who were randomly selected from the schools and classrooms aforementioned, using a questionnaire adapted from the International Study of Asthma and Allergies in Childhood (ISAAC) and the European Community Respiratory Heath Survey (ECRHS). Then, FeNO levels were measured, induced sputum samples were collected and IgE-mediated allergy (allergic skin tests) were conducted concurrently with environmental monitoring. Sputum samples were further analysed to investigate the expression of CD11b, CD35, CD63 and CD66b on both eosinophil and neutrophil using flow cytometry techniques. The 2-level logistic regression (school and children) analysis, general linear regression, and logistic regression with complex sampling were used determining the influencing factors. The results showed that temperature, NO2, PM10, PM2.5 and formaldehyde concentrations in schools located in the urban areas were significantly higher than in the suburban areas. However, all indoor parameters for both areas were below the local and international recommendation guidelines, except for formaldehyde. In the profile analysis, the fungal diversity levels were significantly abundant in suburban samples than the urban, in which Aspergillus clavatus (37.8%) and Hyphoderma multicystidium (13.6%) were dominant. Moreover, regression analysis revealed that the manifestations of wheezing, eczema, rhinitis and nasal infection were associated with PM10 (OR = 1.08, 95% CI = 1.01 - 1.17), CO2 (OR = 1.03, 95% CI = 1.01 - 1.05), formaldehyde (OR = 1.10, 95% CI = 1.03 - 1.17), the relative abundance of Xenasmatella ardosiaca (OR = 1.40, 95% CI = 1.09 - 1.81) and Cladosporium halotolerans (OR = 27.43, 95% CI = 2.21 - 340.87), and a few indoor home environment factors. This study also found that the expression profile of CD11b, CD35, CD63 and CD66b on eosinophil and neutrophil cells were influenced by indoor pollutants and several fungal taxa (Trichosporon asahii (OR = 4.01, 95% CI = 1.02 - 16.45), Hannaella pagnoccae (OR = 3.33, 95% CI = 1.05 - 10.55), Hazslinszkyomyces aloes (OR = 7.58, 95% CI = 9.80 - 58.76), Papiliotrema bandonii (OR = 3.78, 95% CI = 1.77 - 8.06), Candida parapsilosis (OR = 1.94, 95% CI = 2.12-18.31)) after controlling for confounders. Overall, this study demonstrated that many rare and unculturable fungi taxa together with exposure to indoor air pollutants were potentially attributable to an increase in the airway inflammation reactions and the manifestation of asthma development among school children. The novelty of this study lies in the inclusion of rare and unculturable fungi taxa data characterised from metagenomics protocols, and multi-dimensional expression data of adhesion molecules (CD11b, CD35, CD63 and CD66b) analysed using flow cytometry, whilst simultaneously evaluated with indoor pollutant parameters using a regression for complex samples to enhance health risk assessment of these school children. In this context, future endeavors to determine the prolonged effects and patterns of inflammatory biomarkers in relation to indoor air pollutants are warranted.